The evaluation of the learning of the students of the Bachelor's degree in Executive Secretariat: a perception by the norms (Research, Society and Development, 2020)
The present research investigated and identified the perception of the evaluation concept used by IFMT through the laws, rules and institutional resolutions, the evaluation process of the Bachelor's Degree in Executive Secretariat of the IFMT Campus Cuiabá was also analyzed. Thus, there was a bibliographic and documentary survey on the process of assessing learning in relation to national laws and standards. Analyzing the evaluation process regulated by the IFMT, verifying its resolutions and general guidelines, investigating and exploring the perception of evaluation of the pedagogical project of the course presented. The research was developed with the objective of identifying the perception of learning assessment through the IFMT rules and regulations. She also intends to collaborate with the learning evaluation process adopted in the Bachelor Course in Executive Secretariat of Campus Cuiabá / IFMT. In the end, it was concluded that the IFMT has a conception of dialogical, formative, procedural and continuous evaluation, which presupposes the contextualization of the knowledge and activities developed and is in accordance with the current rules and legislation. It was suggested, with the research, a reformulation of the Pedagogical Course Project (PPC) with a focus on improving and clarity of the evaluation process to be in accordance with the guidelines of the didactic organization of the institution. Thus, the student will be able to perceive the general and local overview of the evaluation process, having clarity in the PPC of the methods and instruments used for its evaluation, being able to reflect and plan his studies with more autonomy.